1993
DOI: 10.1073/pnas.90.20.9359
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type-specific expression of rat steroid 5 alpha-reductase isozymes.

Abstract: The enzyme steroid 5a-reductase (EC 1.3.99.5) is a component of an intercellular signaling pathway that determines cell fate in the primordium of the mammalian reproductive tract. During male phenotypic sexual differentiation, the dihydrotestosterone product of this enzyme binds to the androgen receptor and initiates development of the external genitalia and prostate. Genes encoding two isozymes of steroid 5a-reductase with different biochemical properties and tissue distributions have recently been isolated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 25 publications
(30 reference statements)
3
29
1
Order By: Relevance
“…Although there is a preponderance of type 2 expression in primate epididymis (Mahony et al 1997(Mahony et al , 1998, both isozymes are still present, and men with a deficiency of the type 2 enzyme develop epididymis (Thigpen et al 1992). Similarly, both isozymes are expressed in rat epididymis (Berman & Russell 1993, Viger & Robaire 1996. Further studies investigating isozyme expression of 5α-reductases in other accessory sex glands are necessary to determine the patterns and relative levels in the male reproductive tract of the horse.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a preponderance of type 2 expression in primate epididymis (Mahony et al 1997(Mahony et al , 1998, both isozymes are still present, and men with a deficiency of the type 2 enzyme develop epididymis (Thigpen et al 1992). Similarly, both isozymes are expressed in rat epididymis (Berman & Russell 1993, Viger & Robaire 1996. Further studies investigating isozyme expression of 5α-reductases in other accessory sex glands are necessary to determine the patterns and relative levels in the male reproductive tract of the horse.…”
Section: Discussionmentioning
confidence: 99%
“…Reports as to the cellular location of 5 R are also controversial: in rat, 5 R-I is in basal epithelial cells and the 5 R-II in stroma (Berman & Russell 1993). Silver et al (1994) have reported that human 5 R-II in some BPH specimens is predominantly in the basal epithelial cells whereas in other specimens it is in both stroma and basal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This cell type specificity is characteristic of multiple embryonic structures in the reproductive tract including the genital tubercle/ phallus (Figs. 1-5), urogenital sinus, prostate, vagina, and bulbourethral gland (Berman et al, 1995), and the epididymis and prostate of the adult male animal (Berman and Russell, 1993). In the case of the genital tubercle, epithelia derived from both the ectoderm (e.g., cells of the surface epithelium, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of the 5a-reductase type 1 antibody is documented in Berman and Russell (1993). Exposure times for the in situ mRNA hybridization experiments ranged from 10 to 21 days.…”
Section: In Situ Mrna Hybridization and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation